A Rare Eyeball Luxation After Cranioplasty and a Four-Year Follow-Up. Issue 6 (September 2017) - Yin, Lin; Zhang, Zhiyong; Liu, Wei; Tang, Xiaojun; Yin, Hongyu; Feng, Shi
Abstract : Abstract: A rare patient of reducible eyeball luxation after cranioplasty in a child Crouzon syndrome was reported. To remedy the patient's chronic intracranial hypertension and brachycephaly, orbitofrontal advancement and cranial vault remodeling were carried out. About 25 days of postoperation, an acute eyeball luxation was observed, with the presence of a subcutaneous accumulation of liquid in the bilateral temporal regions. The dislocated eyeballs were brought back by applying gentle manual pressure. The patient received a conservative treatment without a tarsorrhaphy. The dislocation recurrence never occurred again. In a 4-year follow-up, it was shown that the child's vision was normal and proptosis was improved by series craniofacial reconstructions.